Annexin A1, A2, A5, and A6 involvement in human pathologies - de Souza Ferreira, Luiz Philipe (2023)
The human genome codes for 12 annexins with highly homologous membrane-binding cores and unique amino termini, which endow each protein with its specific biological properties. Not unique to vertebrate biology, multiple annexin orthologs are present in almost all eukaryotes. Their ability to combine either dynamically or constitutively with membrane lipid bilayers is hypothetically the key property that has led to their retention and multiple adaptation in eukaryotic molecular cell biology. Annexin genes are differentially expressed in many cell types but their disparate functions are still being discovered after more than 40 years of international research. A picture is emerging from gene knock down and knock out studies of individual annexins that these are important supporters rather than critical players in organism development and normal cell and tissue function. However, they appear to be highly significant “early responders” toward challenges arising from cell and tissue abiotic or biotic stress. In humans, recent focus has been on involvement of the annexin family for its involvement in diverse pathologies, especially cancer. From what has become an exceedingly broad field of investigation, we have selected four annexins in particular: AnxA1, 2, 5, and 6. Present both within and external to cells, these annexins are currently under intensive investigation in translational research as biomarkers of cellular dysfunction and as potential therapeutic targets for inflammatory conditions, neoplasia, and tissue repair. Annexin expression and release in response to biotic stress appears to be a balancing act. Under- or over-expression in different circumstances appears to damage rather than restore a healthy homeostasis. This review reflects briefly on what is already known of the structures and molecular cell biology of these selected annexins and considers their actual and potential roles in human health and disease.